Palliative and End of Life Care Competencies Among Nurses in Surgical Transplant Units - Alday, Cecille Lumbera; JB, Cabatotan; M, Abshari; G, Pascua; APL, Blaquera (Proceedings Series on Health & Medical Sciences, 2025)
Background: Palliative care is an essential part of modern healthcare. As communicable and non-communicable diseases increase and the population ages, the need for palliative care continues to grow. Nurses must therefore have strong competencies in providing this type of care. While palliative care is commonly associated with cancer patients, little research has examined the palliative care skills of nurses working in surgical transplant units. Purpose: This study aims to determine the palliative and end-of-life care competencies among nurses in surgical transplant units. Methods: A quantitative cross-sectional research design is employed. The data is collected from surgical transplant nurses using Microsoft Forms, specifically those related to Health and Social Care, Living Matters, Dying Matters, and the Palliative and End-of-life competency assessment tool, and distributed through the participants’ personal email. Health and Social Care, Living Matters, Dying Matters, and Palliative and End-of-life competency tool. The t-test, ANOVA, Mann-Whitney U test, and Games-Howell post hoc test are utilized to analyze the results. Results: A total of 188 nurses in the surgical transplant unit participated in this study. Most of the participants were female (84.04%), aged 30 to 39 years (68.62 %), held a bachelor’s degree (85.11%), and had over 11 years of experience (77.13%). Notably, 67.02% lacked formal training in palliative and end-of-life care. Competency scores were generally strong, with communication skills (mean=2.65) and symptom management (mean=2.58) rated highest. Competency varied significantly based on age, education, position, and training. The primary challenges include managing family dynamics (72.34 %) and lack of training 14.89%). Conclusion: The participants’ palliative and end-of-life care competency across all measured domains is highly developed. Age, educational attainment, position, and training have a significant impact on nurses’ competence. Family dynamics is identified as the primary challenge in dealing with palliative and end-of-life patients. Training and education are needed to improve staff competence and ensure high-quality palliative care.